Synthesis, Characterization and Thermal Behavior of Carbon Fiber Reinforced Poly(vinyl chloride) and Poly(?-Caprolactone) - Pekdemir, Mustafa Ersin (Korean Fiber Soc, 2021)
In this study, composites of carbon fiber (CF) with poly vinyl chloride (PVC), poly(epsilon-caprolactone) (PCL), and 1:1 ratio of PVC/PCL blend were prepared. The composites were characterized by ATR-IR, SEM-EDX, XRD, and Electrical Resistivity techniques. Ozawa-Flynn-Wall (OFW) method was used to calculate the activation energy (E-a) of the composites from thermogravimetry (TG) curves. The activation energies of CF/PVC, CF/PCL, and CF/Blend composites were 89 kJ/mol, 61 kJ/mol, and 72 kJ/mol, respectively. From the DSC curves, it was determined that glass transition (T-g) values of composites prepared with CF were higher than pure polymers. Additionally, CF/Blend had a melting temperature of 54.8 degrees C due to the dissolution of PVC in the molten PCL. In SEM images, it was clearly seen that the polymer matrix consisting of PVC and PCL was attached to the CF surfaces. The XRD results showed that the peak (002) at 2 theta=25 degrees represents the characteristic CF, while another peak (110) at 2 theta=22 degrees denotes the CF/PCL composite. The electrical resistivity of CF/PVC, CF/PCL and CF/Blend composites were 0.1714, 0.0873, and 0.0318 Omega mm, respectively.
Keywords: Carbon fiber; Poly(vinyl chloride); epsilon-caprolactone; Blend; Composite